When twilight comes : the animals and plants that bring dawn and dusk to life - Atkins, Marcie Flinchum (Chronicle Books, 2026)
When twilight comes, nature transitions: from night to day at dawn and from day to night at dusk. Inside our homes, we are getting ready to start our days or end them, but outside, crepuscular creatures--animals that are most active at dawn or dusk--are right in the middle of their days! This engaging nonfiction picture book shows familiar animals and beautiful flowers--skunks, white-tailed deer, fireflies, morning glories, evening primroses, and more--in a whole new light, focusing on the behaviors, adaptations, and activities that define each as a crepuscular creature or plant. The lushly illustrated pages demonstrate the interconnected interactions between critters and their environments, powerfully showing how each is essential to the ecosystem as a whole. From the first page welcoming the dawn to the last page beckoning us to venture outside during the magical in-between times, this mesmerizing book encourages young readers to compare and contrast the rhythms of the natural world with the rhythms of their own days, inviting curiosity and encouraging comfort with transition times.